TEKNOLOGI PEMBUATAN KOMPOS KOTORAN SAPI SIMENTAL DENGAN PENGGUNAAN TITHONIA (Thitonia diversifolia) DAN MOL REBUNG PADA KELOMPOK TANI TERNAK - Ade Rakhmadi; Allismawita Allismawita; Indri Juliyarsi (LPPM Universitas Andalas, 2018)
Community service is counseling. By taking the title: Counseling Addition of Tithonia (Thitonia diversifolia) and MOL Rebung On Making Simmental Cow Manure Compost Livestock Farming Group In-Kanagarian Koto Baru Kecamatan Sungai Tarab Kabupaten Tanah Datar. This counseling is motivated by farmers in Kanagarian Koto Baru farmers to obtain fertilizer. Besides the expensive price of fertilizer is also difficult to obtain. So from that background people want to change from buying inorganic fertilizer to organic fertilizer like compost. Compost is an easy organic fertilizer. In the making takes 4-6 months. This can be shortened by the use of compost starters such as EM4 and stardex. However, this compost starter is expensive and difficult to obtain. For that then MOL (Micro Organism Local) Rebung can replace the starter is expensive. In addition to low prices, MOL Rebung is easily bred. Simmental cattle dung is the raw material of compost fertilizer. However, it still has a low nutrient. For that plus tithonia as an addition element haranya. Counseling in Kanagarian Koto Baru get great enthusiasm from the community, because the community is in dire need of compost. In counseling the community is taught to multiply the MOL starter from Rebung. This starter propagation uses bamboo shoots, brown sugar and rice washing water as the medium.